Decatransin, a new natural product inhibiting protein translocation at the Sec61/SecYEG translocon - Junne, Tina (J Cell Sci, 2015)
A new cyclic decadepsipeptide was isolated from Chaetosphaeria tulasneorum with potent bioactivity on mammalian and yeast cells. Chemogenomic profiling in S. cerevisiae indicated that the Sec61 translocon complex, the machinery for protein translocation and membrane insertion at the endoplasmic reticulum, is the target. The profiles were similar to those of cyclic heptadepsipeptides of a distinct chemotype (including HUN-7293 and cotransin) that had previously been shown to inhibit cotranslational translocation at the mammalian Sec61 translocon. Unbiased, genome-wide mutagenesis followed by full-genome sequencing in both fungal and mammalian cells identified dominant mutations in Sec61p (yeast) or Sec61α1 (mammals) that conferred resistance. Most, but not all, of these mutations affected inhibition by both chemotypes, despite an absence of structural similarity. Biochemical analysis confirmed inhibition of protein translocation into the endoplasmic reticulum of both co- and post-translationally translocated substrates by both chemotypes, demonstrating a mechanism independent of a translating ribosome. Most interestingly, both chemotypes were found to also inhibit SecYEG, the bacterial Sec61 translocon homolog. We suggest ‘decatransin’ as the name for this new decadepsipeptide translocation inhibitor.